Social media addiction - Steffens, Bradley, 1955- (Risks of social media., 2021)
"Social media addiction is a behavioral addiction similar to gambling disorder, gaming addiction, and shopping addiction. A behavioral addiction is a mental health condition in which a person repeatedly engages in a particular behavior, even if the behavior causes them harm"--